Perancangan Media Pembelajaran Pengenalan Mikrokontroler Menggunakan Augmented Reality pada Mata Pelajaran Sistem Komputer - Ronaldo, Patrisius Jones; Wijaya, Indra; Menrisal, M (SAFE-Network, 2023)
This study aims to determine the validity, practicality, and effectiveness of designing microcontroller introduction learning media in computer systems subjects. This research uses research development method (Research & Development). The research subjects were 62 students of class X TKJ SMK Negeri 2 Padang. The results of the assessment of the three validators as a whole are 83.00%, so that the level of validity can be interpreted as valid. The results of the overall practicality test assessment are 88.03%, so that the practicality level can be interpreted as Very Practical to use. The results of the overall effectiveness test assessment are 92.90%, so that the level of effectiveness can be interpreted as very effective in use.